The Effect of Government Reference Bonds on Corporate Borrowing Costs: Evidence from a Natural Experiment - Flannery, Mark J.; Hong, Claire Yurong; Wang, Baolian (Management Science, 2023)
Government bonds might provide reference entities that reduce corporate bond yields. We study China’s 2017 issuance of two U.S. dollar (USD)-denominated sovereign bonds when there were (effectively) no outstanding USD sovereigns. We find that Chinese corporate USD bonds experienced a four- to nine-basis-point decline in yield spreads, whereas corporate renminbi (RMB) bonds did not. The effect was stronger for corporate bonds with maturities similar to those of the USD sovereigns. Further consistent with the reference effect, USD-denominated corporate bonds experienced declines in bid-ask spreads and volatility; corporate bond yield spread changes became more sensitive to sovereign yield innovations; and the less-informed foreign mutual funds significantly increased their holdings of offshore USD Chinese corporate bonds. Limited evidence indicates that new corporate bond maturities shifted toward the sovereign bonds’ maturity after their issuance. This paper was accepted by Lukas Schmid, finance. Funding: B. Wang received financial support from Hong Kong Institute for Monetary Research. C. Y. Hong received financial support from the National Natural Science Foundation of China [Grant 72003125]. Supplemental Material: The internet appendix and data are available at https://doi.org/10.1287/mnsc.2022.4499 .